Training sessions of volunteer dairy farmers during the workshops lauching the 2024 campaign of experimentation of agroecological technologies - Ouattara Songdah, Désiré; Sib, Ollo; Traore, Issouf; Ouattara, Baba; Vall, Eric (2024)
In systems oriented towards dairy production, forage biodiversification, crop-livestock interaction and co-product recycling are key agroecological factors that can combat low cow productivity and the seasonality of milk production (Sib et al., 2017; Vall et al., 2021; Sodre et al., 2022; Vall et al., 2023). In 2023, as part of the Initiative on agroecology project, a loop and cascade approach to action on dairy farms was implemented to co-design more agroecological dairy farming systems with dairy farmers in Burkina Faso. An On-farm Experimental Design for Agroecology (OnEDA ; Dispositif Expérimental Agroécologique en Milieu Paysan – DEAMP in french) was set up with volunteer farmers. The OnEDA consisted of: 1) a forage and seed production system called Fodder Demo-Plot (FDP); 2) advice on the rational management of the farm's plant and animal co-products using the CoProdScope tool (Zoungrana et al., 2023); 3) advice on dairy cow ration management using the Jabnde tool implemented in Dairy Production Workshops using FDP fodder and 4) Efficient Covered Manure Pits with monitoring of the recycling of animal and plant coproducts from production and the use of organic manure.